Platelet-Rich Plasma as a Novel Treatment for Hair Loss: A Systematic Review of Safety, Efficacy, and Patient Outcomes - Claudia Felicia Limanda; Ericko Hartanto; Jeanny Megawati Soewardy; Alya Ihsani Harahap (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Hair loss is common and clinically heterogeneous, and platelet-rich plasma (PRP) has emerged as a minimally invasive autologous therapy with potential effects on follicular cycling and the scalp microenvironment. This review evaluated PRP safety, efficacy, and patient outcomes across hair-loss conditions. Methods: PRISMA-guided systematic review and meta-analysis was conducted using PubMed, Embase, and Scopus (inception to 10 February 2026). Human clinical studies with extractable quantitative data on PRP for hair loss were included. Primary outcomes were hair density, hair thickness, hair count, and pulled hair number; safety and patient-reported outcomes were summarized. Risk of bias was assessed using ROBINS-I, and random-effects models were applied for pooling. Result: Eight studies met inclusion criteria. PRP was generally well tolerated, with mostly mild, transient procedure-related adverse events (e.g., injection-site pain, erythema/edema, pruritus, bruising) and no consistent signal of serious complications, although safety reporting was variable. Meta-analysis showed PRP increased hair density (pooled SMD = 3.39, 95% CI 2.27–4.52) and hair thickness (pooled SMD = 2.78, 95% CI 1.91–3.65) versus control, and reduced pulled hair number (pooled SMD = −3.75, 95% CI −5.59 to −1.92). Hair count was not clearly different from control (pooled SMD = −0.95, 95% CI −17.87 to 15.96). Most studies were at low-to-moderate risk of bias, with one at serious risk. Conclusions: PRP may improve hair density and thickness and reduce shedding-related measures in selected patients, but effects on hair count remain uncertain and outcomes are sensitive to protocol variability. Larger standardized randomized trials with longer follow-up are needed.